226k views
4 votes
Whats the answer??? And how do i solve it!

Whats the answer??? And how do i solve it!-example-1

1 Answer

4 votes

Answer:


\large\boxed{3^(2)/(3)}

Explanation:


Use\\\\\sqrt[n]{a^m}=a^(m)/(n)\\\\(a^n)^m=a^(nm)\\\\a^n\cdot a^m=a^(n+m)\\\\\bigg(\sqrt[4]{9^(15)}\cdot√(3^3)\bigg)^(2)/(27)=\bigg(\sqrt[4]{(3^2)^(15)}\cdot3^(3)/(2)\bigg)^(2)/(27)=\bigg(\sqrt[4]{3^(2\cdot15)}\cdot3^{(3)/(2)}\bigg)^(2)/(27)\\\\=\bigg(3^{(30)/(4)}\cdot3^(3)/(2)\bigg)^(2)/(27)=\bigg(3^{(15)/(2)}\cdot3^(3)/(2)\bigg)^(2)/(27)=\bigg(3^{(15)/(2)+(3)/(2)}\bigg)^(2)/(27)


=\bigg(3^{(18)/(2)}\bigg)^(2)/(27)=\bigg(3^9\bigg)^(2)/(27)=3^{9\cdot(2)/(27)}=3^(2)/(3)

User Tarique Naseem
by
6.3k points